Cascading Climate Resilience: A Training of Trainers Approach to Integrate Climate Risk Management in Ethiopia’s Agricultural Extension - Belay, Berhanu; Demissie, Teferi; Solomon, Dawit (International Livestock Research Institute, 2024)
A Training of Trainers (ToT) approach was implemented across 69 watersheds within the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) Climate-sensitive Innovations for Land Management Program (CLM) project areas to effectively disseminate skills and knowledge on Climate Risk Management in Agricultural Extension (CRMAE). The GIZ-CLM watersheds spread in eight regions of Ethiopia, namely Southern Ethiopia, Sidama, Central Ethiopia, Tigray, Amhara, Oromia, Benishangul Gumuz, and Gambela. In this ToT approach, the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), in collaboration with 12 public universities and 38 staff of universities, trained 814 staff from the Ministry of Agriculture (MoA) and GIZ on CRMAE. AICCRA and its partners undertook the ToT training based on the request received from the GIZ under the CLM project and Norwegian Church Aid (NCA) in collaboration with the Ethiopian Orthodox Church Development and Inter-Church Aid Commission (EOTC-DICAC). The knowledge and skills acquired by MoA-GIZ staff were subsequently used to train over 23,117 beneficiaries, with primary aim of facilitating the integration of climate risk knowledge into their respective watershed activity plans. The direct beneficiaries of these trainings included 681 leaders of watershed user committees, 1,854 participants in climate risk assessment and adaptation planning, 1,410 members of the plan updating and revision team, 3,763 individuals involved in plan endorsement for action, and 15,302 smallholder farmers engaged in climate-sensitive watershed management. The cascading effects of the ToT modality proved effective in reaching a larger number of end-users within a short timeframe and fostered strong collaboration among diverse stakeholders. It is also a key to transform the memorandum of understanding into actionable commitments. This experience should, therefore, be shared among agricultural extension institutions to promote broader adoption of the ToT approach within the Ethiopian extension system.